2010
DOI: 10.1063/1.3359649
|View full text |Cite
|
Sign up to set email alerts
|

Threshold voltage in short channel polycrystalline silicon thin film transistors: Influence of drain induced barrier lowering and floating body effects

Abstract: The threshold voltage (VT) variations induced by the drain bias (Vds) are investigated in polycrystalline silicon thin film transistors (TFTs), with channel length ranging from 20 to 0.4 μm, by combining experimental measurements and two-dimensional (2D) numerical simulations. A careful analysis of the electrical characteristics in both subthreshold and off regime is performed, by taking in account also the effects of the leakage current field enhanced mechanisms on the overall generation-recombination rate. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The p + source and drain regions were formed by B implant (a dose of 10 15 cm −2 ) through the oxide film, with the gate acting as a mask, and dopant activation was obtained by a second pass through the excimer laser. The effective channel length of the devices was 100 nm shorter than the nominal one L [7]. Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The p + source and drain regions were formed by B implant (a dose of 10 15 cm −2 ) through the oxide film, with the gate acting as a mask, and dopant activation was obtained by a second pass through the excimer laser. The effective channel length of the devices was 100 nm shorter than the nominal one L [7]. Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Self-aligned p-channel polysilicon TFTs were fabricated, according to the process already reported in [7]. The 40-nmthick active layer was crystallized by excimer laser annealing, and the gate oxide, 60 nm thick, was deposited by PECVD at 300 • C using SiH 4 and N 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that V t is significantly decreased with higher V d for low-voltage devices, especially for channel length of 3 and 5μm. The DIBL effect which is defined as dV t /dV d is significant because the p-body is lightly doped in these devices [3]. On the other hand, the HV devices, even with L ch = 3 μm, do not show DIBL effect because most of the voltage drop is supported by RESURF region.…”
Section: Device Structure and Experiments Results Device Structurementioning
confidence: 99%
“…In silicon‐on‐insulator structures like typical LTPS TFTs, the generated holes can be piled up, and this leads to inducing more a positive bias to the substrate. Consequently, V th decreases due to the high drain bias [5].…”
Section: Introductionmentioning
confidence: 99%